Optical dating of young feldspars: the zeroing question - Ollerhead, J.; Huntley, D. J. (Ancient TL, 2011)
We present evidence that when using 1.4 eV excitation for optical dating of young K-feldspars, one must recognize that the state of the mineral after a long light exposure depends on the spectrum of that light. Hence, a modern analogue is necessary for the determination of the equivalent dose. In particular, it is required for determining the spectrum of light exposure to be used for the thermal transfer correction.